Polynomial composites and certain types of fields extensions - Matysiak, Ł. (Carpathian Mathematical Publications, 2023)
In this paper, we consider polynomial composites with the coefficients from KL. We already know many properties, but we do not know the answer to the question of whether there is a relationship between composites and field extensions. We present the characterization of some known field extensions in terms of polynomial composites. This paper contains the open problem of characterization of ideals in polynomial composites with respect to various field extensions. We also present the full possible characterization of certain field extensions. Moreover, in this paper we show that any finite group is a Galois group of some field extensions and present the inverse Galois problem solved.